Notes on the Annual Meeting of the ENFSI Expert Working Group for Forensic Information Technologies - N. A. Khatuntsev; E. S. Karpukhina (Теория и практика судебной экспертизы, 2016)
The paper sums up the outcomes of the Annual Meeting of the European Network of Forensic Science Institutes (ENFSI) Forensic Information Technology Working Group. The meeting was held on September 20–23, 2016 in Windsor (the UK).